Collaboration-Generative Disaster Risk Reduction and Management Center of Ilocos Sur - Chan, Randolf Cedric L.; Ong, Simoun T. (Quezon City College of Architecture, University of the Philippines Diliman, 2024)
The Philippines is one of the countries with the most risk due to natural disaster, and in the case of Ilocos Sur, it is susceptible to disasters like earthquake, storms, tsunamis, and its further effects like liquefaction, storm surges, and landslides; however, the provincial and municipal governments as well as its inhabitants lacks the capacity to prevent, mitigate, prepare, respond, and recover for an upcoming or sudden disaster. The project aims to provide the necessary risk reduction facilities, spatial requirements, and interventions to ensure a continuously functioning, adaptable, and efficient development accommodating different DRRM activities that would capacitate, prepare, and respond to different disasters. The design approach is envisioned to incorporate elements of survivability, adaptability, and order. With this, the concept of epicentro is proposed to allow spaces to have a centralized top-down approach to disasters. By having a disaster risk reduction and management-centered development, risk reduction activities are prioritized. In the long run, the project aims to reduce disaster risks that also reduces destruction or loss of life and property in the community up to the provincial level.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Disaster Risk Reduction and Management -- Ilocos Sur; Risk management -- Ilocos Sur